Body Height and Its Estimation Utilizing Arm Span Measurements in Bosnian and Herzegovinian Adults - Stevo Popovic; Dusko Bjelica; Gabriela Doina Tanase; Rajko Milašinović (Montenegrin Sports Academy, 2015)
Anthropologists recognized the tallness of nations in the Dinaric Alps long time ago. As the modern Bosnian and Herzegovinian fall more into the Dinaric racial classification, the purpose of this study was to examine the body height in Bosnian and Herzegovinian adults as well as the relationship between arm span as an alternative to estimating the body height and body height, which vary in different ethnic and racial groups. The nature and scope of this study analyzes 212 students (178 men, aged 22.42±2.79 and 34 women, aged 21.56±2.06) from the University of Banjaluka to be subjects. The anthropometric measurements were taken according to the protocol of the ISAK. Means and standard deviations were obtained. A comparison of means of body heights and arm spans within each gender group and between genders were carried out using a t-test. The relationships between body height and arm span were determined using simple correlation coefficients and their 95% confidence interval. Then a linear regression analysis was performed to examine the extent to which the arm span can reliably predict body height. The results have shown that male Bosnian and Herzegovinians are 183.87±7.11 cm tall and have an arm span of 184.50±8.28 cm, while female Bosnian and Herzegovinians are 171.82±6.56 cm tall and have an arm span of 169.85±8.01 cm. Compared to other studies, the results of this one have shown that both genders make Bosnian and Herzegovinian population one of the tallest nations on the earth, maybe the tallest one. Moreover, the arm span reliably predicts body height in both genders. However, the estimation equations, which were obtained in Bosnian and Herzegovinians, are substantially different alike in other populations, since arm span was close to body heights: in men 0.73±1.17 cm more than the body height and in women 1.97±1.45 centimeters less than the body height. This confirms the necessity for developing separate height models for each population.